(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The demands of the work to health workers of the Pharmacist Assistant are very varied, not only serving and concocting recipes. But, also have to be replaced by the position of a temporary pharmacist with considerable responsibility. The work target is oriented especially in the Jakarta area Pharmacist Assistants who have a greater income achievement than other regions. This makes the Pharmacist Assistant must help each other in problem solving at the Pharmacy in order to be able to serve patients well for the progress of the Pharmacy. But, not all pharmacists have the same behavior . There is a Pharmacist Assistant who is " indifferent ", does not care about his teammates, but there are also those who are happy to help, and care about the problems. The purpose of study was to determine the influence of emotional intelligence to organizational citizenship behavior (OCB) in health care pharmacist assistants. The method of this research is non-experimental quantitative, including in causal research. The sampling technique used proportional random sampling technique. The results showed a significant positive effect of emotional intelligence on OCB (Y = 26,706 + 0.556X) with a sig value. 0,000 and r² = 0.382. Emotional intelligence has an influence on OCB of 38.2% and the rest is influenced by other factors not examined in this study. Pharmacist assistants who have high emotional intelligence are high OCB, but on the contrary if the Pharmacist Assistant has low emotional intelligence, OCB is low. The dominant dimension of OCB that appears in Pharmacist Assistants is sportsmanship.